Pemberdayaan Petani Sayur Melalui Integrasi Azolla-Ikan Dengan Budikdamber - sri Utami Lestari; Neng Susi; Muryanto Muryanto (Asosiasi Dosen Akuntansi Indonesia, 2020)
Maximizing the use of existing land is also an effort to increase income for farmers. When space becomes limited in starting a business / side business, using a bucket is considered the best solution, which is known as Budikdamber. The use of a bucket as a substitute for a pool is to saves space. The problems faced by partners are: lack of skills and knowledge regarding land optimization through Budikdamber technology. Regarding partner problems, a solution to the problem is needed, among others: increase partner knowledge and skills about budikdamber. The method of implementation includes material provision and practice of budikdamber. For the sustainability of this program the PKM team will carry out: monitoring and evaluation of program implementation and assistance. Based on the results of the team's monitoring and evaluation, the following conclusions can be drawn: participants' attendance in the socialization activities adjusted to government regulations during the Pandemic by following health protocols where participants were limited to only 5 people. Participants are very active during the activity, where participants show good enthusiasm during the discussion about the material given regarding the cultivation of azolla and fish in buckets, After the activities the partners have sufficient knowledge and understanding to carry out Budikdamber activities independently or in groups in the future in their respective homes. It is suggested that it is necessary to carry out further activities regarding cultivation and processing of fish into products that have high economic value.